Associations of social capital and health at a city with high aging rate and low population density - Jun-ichiro Watanabe; Takashi Kimura; Takahiro Nakamura; Daisuke Suzuki; Takashi Takemoto; Akiko Tamakoshi (Elsevier, 2022)
Maintaining physical and mental health of older people is one of the important issues to be addressed in the aging society. Social capital, defined as the resources available to members of social groups, has recently attracted attention as a factor influencing public health. Most of the previous studies targeted various communities having different aging rates or population densities at once to examine the associations of social capital and health outcomes. However, the results of those studies are not always consistent. Moreover, because few studies have targeted a particular advanced aging society, associations of social capital and health at such societies have remained unknown. This study examined how social capital associates with health at a particular city having a very high aging rate and low population density. We targeted Iwamizawa city, Hokkaido, Japan, which is one of the most advanced aging areas, with an aging rate of 36.6% and a population density of 165/km2. We analyzed self-administered questionnaire data obtained from "HELLO (HEalth, Lifestyle, and LOcal community of Iwamizawa citizen) Study" in 2018. The sample comprised 1237 individuals aged 65 and older. Following previous studies, we regarded three items-social cohesion, reciprocity, and civic participation-as social capital indices, and targeted two health outcomes: self-rated health (SRH) and degree of depression. Multilevel Poisson regression analyses were used to calculate prevalence ratios (PRs). We found that at the individual-level, the PR (95% confidence interval) of having poor SRH among those with more civic participation was 0.81 (0.71-0.93), and that of being depressed among those with more social cohesion was 0.32 (0.21-0.51), even after adjusting for compositional factors. We also found that the community-level civic participation significantly correlated with aging rate. Our findings indicate that social capital positively associates with older people's health at the advanced aging city.